Interwar Itineraries Authenticity in Anglophone and French Travel Writing - Wittman, Emily O. (Amherst College Press, 2022)
How people traveled, and how people wrote about travel, changed in the interwar years. Novel technologies eased travel conditions, breeding new iterations of the colonizing gaze. The sense that another war was coming lent urgency and anxiety to the search for new places and "authentic" experiences. In Interwar Itineraries: Authenticity in Anglophone and French Travel Writing, Emily O. Wittman identifies a diverse group of writers from two languages who embarked on such quests. For these writers, authenticity was achieved through rugged adventure abroad to economically poorer destinations. Using translation theory and new approaches in travel studies and global modernisms, Wittman links and complicates the symbolic and rhetorical strategies of writers including André Gide, Ernest Hemingway, Michel Leiris, Isak Dinesen, Beryl Markham, among others, that offer insight into the high ethical stakes of travel and allow us to see in new ways how models of the authentic self are built and maintained through asymmetries of encounter.